Exploring the Connection Between Breastfeeding Practices and Milk Production Levels in New Mothers - Dhea Nazlyta Rusman; Tut Rayani Aksohini Wijayanti; Sulistiyah Sulistiyah (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
The World Health Organization (WHO), UNICEF, and the Ministry of Health strongly advocate for the initiation of breastfeeding within the first hour after birth, exclusive breastfeeding for the first six months, and continued breastfeeding up to two years alongside safe and nutritious complementary feeding. Despite these recommendations, one of the main barriers to achieving exclusive breastfeeding is insufficient breast milk production. This study aimed to investigate the relationship between breastfeeding frequency and milk production adequacy among postpartum mothers. To achieve this, an analytical study with a cross-sectional design was conducted, involving 38 participants. Data was collected through questionnaires that assessed breastfeeding patterns, milk production, and other related factors. The data were analyzed using the Chi-square test to determine any significant associations. The univariate analysis revealed that the majority of postpartum mothers (60.5%) reported irregular breastfeeding patterns, and more than half (55.3%) of the participants stated that they experienced inadequate milk production. Further analysis through bivariate tests showed a significant association between the frequency of breastfeeding and the adequacy of milk production, with a p-value of 0.003. This suggests that mothers who breastfeed more regularly may experience better milk production, which can contribute to healthier infant nutrition. These findings highlight the importance of encouraging regular breastfeeding practices in the early postpartum period to enhance milk supply. Improving awareness and providing support for mothers in establishing a consistent breastfeeding routine could play a crucial role in overcoming challenges related to inadequate milk production and achieving the recommended exclusive breastfeeding practices. Further research may be needed to explore other factors that contribute to successful breastfeeding and milk production.